Display device

The display device addresses the issue of insufficient viewing angle compensation by using a specific arrangement of polarizers and slower elements in the elliptical polarizer, ensuring maintained display performance and reduced external light reflection when viewed from various angles.

JP2025039763AActive Publication Date: 2025-03-21SUMITOMO CHEM CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2025003511
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-03-21
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Conventional display devices with optical laminates suffer from insufficient viewing angle compensation, leading to increased external light reflectance and deteriorated display performance when viewed from angles other than directly front.

Method used

A display device configuration that includes a light reflective image display layer and an elliptical polarizer, where the elliptical polarizer is laminated on the image display surface. The polarizers, λ/2 parts, and λ/4 parts are arranged in a specific order, and the λ/2 part is a stacked body of slower elements providing phase differences, ensuring the Nz coefficient of the λ/4 part satisfies a specific relationship with the ρ coefficient.

Benefits of technology

This configuration maintains display performance even when the image is viewed by tilting, effectively preventing external light reflection and ensuring good display quality across a wide range of visible light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039763000001_ABST
    Figure 2025039763000001_ABST
Patent Text Reader

Abstract

To provide a display device capable of maintaining good display performance even when tilting the device to view images.SOLUTION: A display device according to an embodiment includes a light-reflective image display layer, and an elliptically polarizing plate comprising a polarizer, λ / 2 portion, and λ / 4 portion, the λ / 2 portion being a laminate consisting of a first retardant element, second retardant element, second retardant element, and first retardant element stacked in the described order. An Nz coefficient and ρ coefficient of the λ / 4 portion satisfies a relationship represented by an expression (B) when the ρ coefficient of the image display layer is represented by an expression (A): ρ=ReM45 / ReoQ ...(A), 4.5ρ-0.160<Nz<4.5ρ+0.955 ...(B), where ReM45 represents an in-plane retardation for 550 nm wavelength in a projection plane having a tilt angle of 45° with respect to a thickness direction of the image display layer, and ReoQ represents an in-plane retardation of the λ / 4 portion at 550 nm wavelength.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a display device. [Background technology]

[0002] A conventional technique in this technical field is described in Patent Document 1. Patent Document 1 discloses a laminate of a λ / 2 part and a λ / 4 part. The optical laminate described in Patent Document 1 has a phase difference close to λ / 4 over the entire visible light range, and therefore functions as an elliptical polarizing plate with an ellipticity of 97% or more over the entire visible light range when combined with a linear polarizer. If this is placed on a light reflecting layer of an OLED display device or the like, it is possible to suppress external light reflection over a wide range of the visible light range. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] International Publication No. 2018 / 003416 Summary of the Invention [Problem to be solved by the invention]

[0004] The optical laminate described in Patent Document 1 has insufficient viewing angle compensation. Therefore, the performance of the optical laminate described in Patent Document 1 is limited when the display device is viewed from approximately the front, and there is a problem that when the display device is viewed from an inclined position, the external light reflectance increases and the display performance deteriorates.

[0005] An object of the present invention is to provide a display device capable of maintaining display performance even when an image is viewed at an angle. [Means for solving the problem]

[0006] A display device according to one aspect of the present invention comprises: a light-reflective image display layer; and an elliptical polarizing plate laminated on an image display surface of the light-reflective image display layer, the elliptical polarizing plate having a polarizer, a λ / 2 portion, and a λ / 4 portion, the polarizer, the λ / 2 portion, and the λ / 4 portion being arranged in this order from the light-reflective image display layer side, the λ / 4 portion, the λ / 2 portion, and the polarizer; The λ / 2 portion is a laminate in which a first retardation element, a second retardation element, a second retardation element and a first retardation element are laminated in the order of the first retardation element, the second retardation element, the second retardation element and the first retardation element, the first retardation element has a reverse wavelength dispersion and is an element that provides an in-plane retardation of approximately λ / 4, and the second retardation element is an element that provides a thickness direction retardation, the in-plane retardation of the light-reflective image display layer at a wavelength of 550 nm on a projection plane having an inclination angle of 45° with respect to the thickness direction of the light-reflective image display layer is ReM45, the in-plane retardation of the λ / 4 portion at a wavelength of 550 nm is ReoQ, and the ρ coefficient of the light-reflective image display layer is expressed by formula (A), the Nz coefficient of the λ / 4 portion and the ρ coefficient satisfy the relationship shown in formula (B). Display device. ρ=ReM45 / ReoQ (A) 4.5ρ-0.160 <Nz<4.5ρ+0.955 ···(B)

[0007] In the above display device, the Nz coefficient of the λ / 4 portion and the ρ coefficient satisfy the relationship shown in formula (B), and therefore the display performance can be maintained even when an image is viewed at an angle.

[0008] The first retardation element may be a positive A plate that gives an in-plane retardation of approximately λ / 4 at a wavelength of 550 nm.

[0009] The second retarder element may be a positive C plate that imparts a thickness direction retardation.

[0010] The λ / 4 portion is a laminate in which a third retardation element and a first retardation element are laminated in this order from the light-reflective image display layer side, the first retardation element of the λ / 4 portion has a reverse wavelength dispersion and is an element that provides an in-plane retardation of approximately λ / 4, and the third retardation element may be a positive C plate that provides a thickness direction retardation.

[0011] The first retardation element of the λ / 4 portion may be a positive A plate that provides a retardation of approximately λ / 4 as an in-plane retardation at a wavelength of 550 nm, and the third retardation element may be a positive C plate or a negative C plate that provides a thickness direction retardation. Effect of the Invention

[0012] According to the present invention, it is possible to provide a display device capable of maintaining display performance even when an image is viewed at an angle. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 is a schematic diagram showing a schematic configuration of a display device including an optical laminate according to one embodiment. [Diagram 2] FIG. 2 is a schematic diagram showing the positional relationship between the slow axis of the λ / 2 portion, the slow axis of the λ / 4 portion, and the transmission axis of a polarizer. [Diagram 3] FIG. 3 is a diagram for explaining the ρ coefficient of the image display layer. [Figure 4] FIG. 4 is a table showing the results of Examples 1 to 9 and Comparative Examples 1 to 6. [Diagram 5] FIG. 5 is a graph plotting the Nz coefficient against the ρ coefficient in FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] An embodiment of the present invention will be described below. First, the terms used in the present disclosure will be explained.

[0015] [Slow Aiko] In the present disclosure, the retarder refers to an optical medium having birefringence. Birefringence refers to an optical property in which the difference in refractive index between at least two of three orthogonal directions exceeds 0.02.

[0016] [Refractive index of retarder] The refractive indices of the retarder in the three orthogonal directions are referred to as nx, ny, and nz. nx represents the principal refractive index in a direction parallel to the retarder plane in the index ellipsoid formed by the retarder. ny represents the refractive index in a direction parallel to the retarder plane and perpendicular to the direction of nx in the index ellipsoid formed by the retarder. nz represents the refractive index in a direction perpendicular to the retarder plane in the index ellipsoid formed by the retarder.

[0017] [In-plane retardation and thickness retardation of retarder] The retardation Re is a physical quantity that represents the anisotropy of the retarder. Retardation Re includes in-plane retardation Reo and thickness retardation Reth. The in-plane retardation Reo(λ) at a wavelength λ(nm) is expressed by the formula (1), where d represents the thickness (nm) of the retarder. Reo(λ)=(nx−ny)×d (1) The thickness direction retardation Reth(λ) at a wavelength λ(nm) is expressed by the formula (2). d in the formula (2) is the thickness (nm) of the retarder, similar to d in the formula (1). Reth(λ)= ―{nz―(nx+ny) / 2}×d ···(2) The in-plane retardation Reo and the thickness retardation Reth can be adjusted by changing the thickness d of the retarder.

[0018] [Positive A Plate] A positive A plate is a retarder whose refractive index in each direction satisfies the relationship of formula (3). Unless otherwise specified, the slow axis of a positive A plate is parallel to nx, and ny ≒ nz means that the difference between ny and nz is less than 0.02. nx>ny≒nz (3)

[0019] The positive A plate can act as a λ / 4 plate. The λ / 4 plate can have an in-plane retardation of approximately λ / 4 at a wavelength of 550 nm. The in-plane retardation Reo(550) at a wavelength of 550 nm of the λ / 4 plate having an in-plane retardation of approximately λ / 4 can be in the range of formula (4). 92 nm ≤ Reo(550) ≤ 183 nm (4)

[0020] The suitable range of Reo(550) of the λ / 4 plate is preferably 100 nm or more and 160 nm or less, more preferably 110 nm or more and 150 nm or less. The in-plane retardation Reo(λ) and the thickness direction retardation Reth(λ) of the positive A plate at the wavelength λ(nm) have the relationship shown in formula (5) derived from formulas (1), (2), and (3). Reth(λ)=0.5×Reo(λ) ···(5)

[0021] The thickness direction retardation Reth(550) of the λ / 4 plate at a wavelength of 550 nm can be within the range of formula (6). 46 nm ≤ Reth(550) ≤ 92 nm (6)

[0022] The suitable value range of Reth(550) is preferably 50 nm or more and 80 nm or less, and more preferably 55 nm or more and 75 nm or less.

[0023] [Positive C Plate] A positive C plate is a retarder whose refractive index in each direction satisfies the relationship of formula (7). Unless otherwise specified, the slow axis is parallel to nz, and nx≒ny means that the difference between nx and ny is less than 0.02. nx≒ny <nz ··· (7)

[0024] [Negative C plate] A negative C plate is a retarder whose refractive index in each direction satisfies the relationship of formula (8). Unless otherwise specified, the slow axis is in the plane spanned by the nx and ny axes, and the fast axis is parallel to the nz axis. nx≒ny means that the difference between nx and ny is less than 0.02. nx≒ny>nz (8)

[0025] [Wavelength dispersion] The dispersion relationship between wavelength and retardation is also simply called wavelength dispersion. A retarder that satisfies formula (9) and formula (10) is said to have inverse wavelength dispersion, or simply called inverse dispersion. Re(450) / Re(550)≦1.00 (9) 1.00≦Re(650) / Re(550) (10)

[0026] The retarder Re(450) / Re(550) in the present disclosure is preferably 0.90 or less, more preferably 0.85 or less, usually 0.60 or more, preferably 0.70 or more. The retarder Re(650) / Re(550) in the present disclosure is preferably 1.02 or more, more preferably 1.10 or more, usually 1.30 or less, preferably 1.20 or less.

[0027] A retarder that satisfies the formulas (11) and (12) is said to have positive wavelength dispersion, or simply positive dispersion. Re(450) / Re(550)>1.00 (11) 1.00>Re(650) / Re(550) ··· (12)

[0028] [Layer laminate] An optical laminate in which a plurality of retarders are laminated may be called a retarder laminate.

[0029] [Nz coefficient] The Nz coefficient of the retarder can be expressed by the formula (13). Note that the in-plane retardation of the entire retarder laminate at a wavelength λ (nm) (for example, a wavelength of 550 nm) is ReoG, and the thickness direction retardation of the entire retarder laminate is RethG. Nz coefficient ≡(RethG / ReoG)+0.5 (13)

[0030] Next, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same or corresponding parts are designated by the same reference numerals, and duplicated explanations will be omitted. The dimensional ratios of the drawings do not necessarily correspond to those in the description.

[0031] Fig. 1 is a schematic diagram showing a schematic configuration of a display device according to one embodiment. The display device 100 shown in Fig. 1 has a light-reflective image display layer 10 (hereinafter simply referred to as "image display layer 10") and an elliptically polarizing plate 20. In the present disclosure, the elliptically polarizing plate also includes the concept of a circularly polarizing plate.

[0032] [Image display layer] The image display layer 10 forms an image inside and displays the image on the image display surface 10a. The image display layer 10 includes an element structure for forming an image. Therefore, the metal electrode for the wiring portion, the high refractive index layer for the resonator structure of the subpixel, the black matrix, and the like included in the element structure function as a reflecting portion that reflects light. Therefore, the image display layer 10 has light reflectivity that reflects light incident on the display device 100 from the elliptically polarizing plate 20 side, and functions as a light reflecting layer in the display device 100. In this embodiment, the reflected light that is a combination of the light reflected by the metal electrode for the wiring portion, the high refractive index layer for the resonator structure of the subpixel, the black matrix, and the like included in the image display layer 10 as such a light reflecting layer may be referred to as "external reflected light". The image display layer 10 may be flexible so that it can be bent, or may be rigid so that it cannot be bent.

[0033] The image display layer 10 is not limited in terms of layer configuration and materials, etc., as long as it is configured to form an image on the image display surface 10a. The image display layer 10 may be a multi-layered body including a portion (or layer) formed of electrodes and wiring using metals such as gold, silver, copper, iron, nickel, chromium, molybdenum, titanium, aluminum, etc., alloys thereof, etc., a resin film, a bank material, a dielectric portion such as a light-emitting element, and other layers.

[0034] The image display layer 10 may be, for example, a flat panel display device. An example of the flat panel display device is a thin (or panel-shaped) organic electroluminescence display device (hereinafter, also referred to as an "OLED display device"). The display device exemplified as the image display layer 10 is a device that does not include a member for optical compensation on the image display surface.

[0035] When the image display layer 10 is an OLED display device, typically, an electrode (for example, a metal electrode) included in the OLED display device is the reflecting portion. The OLED display device has a thin film structure in which an organic light-emitting material layer is sandwiched between a pair of electrodes facing each other. Electrons are injected into the organic light-emitting material layer from one electrode, and holes are injected from the other electrode, whereby the electrons and holes are combined in the organic light-emitting material layer to emit light by themselves. Of the two electrodes sandwiching the organic light-emitting material layer, the electrode on the image display surface 10a side has a function of transmitting light from the organic light-emitting material layer, while the other electrode has a function of reflecting light from the organic light-emitting material layer toward the image display surface 10a. Therefore, the other electrode typically functions as a reflecting portion in the OLED display device.

[0036] OLED display devices have the advantages of having better visibility than liquid crystal display devices that require a backlight, being able to be made thinner, and being able to be driven by a low DC voltage.

[0037] The elliptically polarizing plate 20 is laminated on the image display layer 10. In the display device 100, an image is viewed from the elliptically polarizing plate 20 side. Therefore, the side opposite the image display layer 10 with respect to the elliptically polarizing plate 20 is also referred to as the "viewing side". The elliptically polarizing plate 20 has a polarizer 31 and an optical laminate 40. As shown in FIG. 1, in the elliptically polarizing plate 20, the polarizer 31 and the optical laminate 40 are arranged in this order from the viewing side.

[0038] The polarizer 31 is laminated on the optical laminate 40. The polarizer 31 can be an absorptive film having a property of absorbing linearly polarized light having a vibration plane parallel to its absorption axis and transmitting linearly polarized light having a vibration plane perpendicular to the absorption axis (parallel to the transmission axis). As the polarizer 31, a film in which a dichroic dye is adsorbed and oriented on a uniaxially stretched polyvinyl alcohol-based resin film can be suitably used. The polarizer 31 can be manufactured by a method including, for example, a step of uniaxially stretching a polyvinyl alcohol-based resin film; a step of dyeing the polyvinyl alcohol-based resin film with the dichroic dye to adsorb the dichroic dye; a step of treating the polyvinyl alcohol-based resin film adsorbed with the dichroic dye with a crosslinking liquid such as an aqueous boric acid solution; and a step of washing with water after the treatment with the crosslinking liquid.

[0039] As the polyvinyl alcohol resin, a saponified polyvinyl acetate resin can be used. As the polyvinyl acetate resin, in addition to polyvinyl acetate, which is a homopolymer of vinyl acetate, copolymers of vinyl acetate with other monomers copolymerizable therewith can be mentioned. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.

[0040] In the present disclosure, "(meth)acrylic" means at least one selected from acrylic and methacrylic. The same applies to "(meth)acryloyl", "(meth)acrylate", etc.

[0041] The thickness of the polarizer 31 is usually 30 μm or less, preferably 15 μm or less, more preferably 13 μm or less, further preferably 10 μm or less, and particularly preferably 8 μm or less. The thickness of the polarizer 31 is usually 2 μm or more, and preferably 3 μm or more.

[0042] As the polarizer 31, for example, as described in JP 2016-170368 A, a dichroic dye may be oriented in a cured film formed by polymerizing a liquid crystal compound. As the dichroic dye, a dye having absorption in a wavelength range of 380 to 800 nm may be used, and it is preferable to use an organic dye. As the dichroic dye, for example, an azo compound may be used. The liquid crystal compound is a liquid crystal compound that can be polymerized while being oriented, and can have a polymerizable group in the molecule. In addition, as described in WO2011 / 024891, a polarizing film may be formed from a dichroic dye having liquid crystal properties.

[0043] The luminosity-corrected polarization degree of the polarizer 31 is preferably 90% or more, and more preferably 95% or more. There is no particular upper limit, but it is 99.9999% or less. The luminosity-corrected single transmittance of the polarizing film is preferably 35% or more, and more preferably 40% or more. There is no particular upper limit, but it is 49.9% or less. When the laminate includes a polarizer 31 with such performance, reflected light is less likely to leak, and coloring can be made less noticeable.

[0044] 1, a protective film 32 may be provided on one or both sides of a polarizer 31. A laminate in which a protective film 32 is laminated on a polarizer 31 may be referred to as a linear polarizing plate 30.

[0045] The protective film 32 may be a thermoplastic resin having light-transmitting properties (preferably optically transparent). The protective film 32 may be a film made of, for example, a polyolefin resin such as a chain polyolefin resin (polypropylene resin, etc.) or a cyclic polyolefin resin (norbornene resin, etc.), a cellulose resin such as triacetyl cellulose or diacetyl cellulose, a polyester resin such as polyethylene terephthalate or polybutylene terephthalate, a polycarbonate resin, a (meth)acrylic resin such as a methyl methacrylate resin, a polystyrene resin, a polyvinyl chloride resin, an acrylonitrile-butadiene-styrene resin, an acrylonitrile-styrene resin, a polyvinyl acetate resin, a polyvinylidene chloride resin, a polyamide resin, a polyacetal resin, a modified polyphenylene ether resin, a polysulfone resin, a polyethersulfone resin, a polyarylate resin, a polyamideimide resin, a polyimide resin, or the like.

[0046] The retardation value of the protective film 32 may be appropriately controlled to a suitable value. In order to improve the visibility of the screen when a user wears polarized sunglasses or the like, the in-plane retardation value at a wavelength of 550 nm may be set to 70 to 140 nm.

[0047] The thickness of the protective film 32 is usually 1 to 100 μm, but from the viewpoints of strength, handleability, etc., it is preferably 5 to 60 μm, more preferably 10 to 55 μm, and even more preferably 15 to 40 μm.

[0048] When protective films 32 are attached to both sides of the polarizer 31, the two protective films 32 may be made of the same type of thermoplastic resin or different types of thermoplastic resin. The two protective films 32 may have the same thickness or different thicknesses. Furthermore, the two protective films 32 may have the same retardation characteristics or different retardation characteristics.

[0049] As described above, at least one of the protective films 32 may have a surface treatment layer (coating layer) such as a hard coat layer, an antiglare layer, a light diffusion layer, an antireflection layer, a low refractive index layer, an antistatic layer, or an antifouling layer on its outer surface (the surface opposite to the polarizer 31). The thickness of the protective film 32 includes the thickness of the surface treatment layer.

[0050] The protective film 32 can be attached to the polarizer 31 via, for example, an adhesive layer or a pressure-sensitive adhesive layer. As the adhesive for forming the adhesive layer, a water-based adhesive, an active energy ray-curable adhesive, or a thermosetting adhesive can be used, and preferably, a water-based adhesive or an active energy ray-curable adhesive. As the pressure-sensitive adhesive layer, the one described below can be used.

[0051] Examples of the aqueous adhesive include an adhesive made of an aqueous polyvinyl alcohol resin solution, an aqueous two-liquid urethane emulsion adhesive, and the like. Among them, an aqueous adhesive made of an aqueous polyvinyl alcohol resin solution is preferably used. Examples of the polyvinyl alcohol resin include a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, a polyvinyl alcohol copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith, and a modified polyvinyl alcohol polymer in which the hydroxyl groups of these are partially modified. The aqueous adhesive may contain a crosslinking agent such as an aldehyde compound (such as glyoxal), an epoxy compound, a melamine compound, a methylol compound, an isocyanate compound, an amine compound, or a polyvalent metal salt.

[0052] When a water-based adhesive is used, a drying step is preferably carried out to remove water contained in the water-based adhesive after bonding the polarizer 31 and the protective film 32. After the drying step, a curing step of curing at a temperature of, for example, 20 to 45° C. may be provided.

[0053] The active energy ray-curable adhesive is an adhesive containing a curable compound that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, and X-rays, and is preferably an ultraviolet ray-curable adhesive.

[0054] The curable compound may be a cationic polymerizable curable compound or a radical polymerizable curable compound. Examples of the cationic polymerizable curable compound include an epoxy compound (a compound having one or more epoxy groups in the molecule), an oxetane compound (a compound having one or more oxetane rings in the molecule), or a combination thereof. Examples of the radical polymerizable curable compound include a (meth)acrylic compound (a compound having one or more (meth)acryloyloxy groups in the molecule), other vinyl compounds having a radical polymerizable double bond, or a combination thereof. A cationic polymerizable curable compound and a radical polymerizable curable compound may be used in combination. An active energy ray curable adhesive usually further includes a cationic polymerization initiator and / or a radical polymerization initiator for initiating the curing reaction of the curable compound.

[0055] When the polarizer 31 and the protective film 32 are bonded to each other, at least one of the bonding surfaces may be subjected to a surface activation treatment in order to enhance adhesion. Examples of the surface activation treatment include dry treatments such as corona treatment, plasma treatment, discharge treatment (glow discharge treatment, etc.), flame treatment, ozone treatment, UV ozone treatment, and ionizing active ray treatment (ultraviolet ray treatment, electron beam treatment, etc.); and wet treatments such as ultrasonic treatment using a solvent such as water or acetone, saponification treatment, and anchor coat treatment. These surface activation treatments may be performed alone or in combination of two or more.

[0056] When the protective films 32 are attached to both sides of the polarizer 31, the adhesive for attaching these protective films 32 may be the same kind of adhesive or different kinds of adhesive.

[0057] The optical laminate 40 is disposed between the polarizer 31 (the linear polarizing plate 30 in the embodiment shown in FIG. 1) and the image display layer 10 in the display device 100. The optical laminate 40 has a λ / 2 portion 41 and a λ / 4 portion 42. The λ / 2 portion 41 and the λ / 4 portion 42 are disposed in this order from the viewing side. In this embodiment, unless otherwise specified, the slow axes of the λ / 2 portion 41 and the λ / 4 portion are parallel to nx.

[0058] 2 is a schematic diagram showing the arrangement relationship between the slow axis 41a of the λ / 2 portion 41, the slow axis 42a of the λ / 4 portion 42, and the transmission axis 31a of the polarizer 31. As shown in FIG. 2, the λ / 2 portion 41 and the λ / 4 portion 42 are arranged such that the angle θ1 between the slow axis 41a of the λ / 2 portion 41 and the slow axis 42a of the λ / 4 portion 42 is approximately 60°. Approximately 60° means a range of 60°±5°. It is preferable that the λ / 2 portion 41 is arranged with respect to the polarizer 31 such that the angle between the slow axis 41a of the λ / 2 portion 41 and the transmission axis 31a of the polarizer 31 is approximately 15°. Approximately 15° means a range of 15°±5°. In this case, the λ / 4 portion 42 is preferably disposed with respect to the polarizer 31 such that the angle θ3 between the slow axis 42a of the λ / 4 portion 42 and the transmission axis 31a of the polarizer 31 is approximately 75°. Approximately 75° means a range of 75°±5°.

[0059] The λ / 2 portion 41 has a function of imparting a phase difference of λ / 2 to the incident light of wavelength λ. The value of the Nz coefficient of the λ / 2 portion 41 is desirably approximately 0.5. The value of the Nz coefficient of approximately 0.5 means that the Nz coefficient is in the range of 0.5±0.1. The preferred range of the Nz coefficient of the λ / 2 portion 41 is 0.45 or more and 0.55 or less. Unless otherwise specified, the slow axis of the λ / 2 portion 41 is parallel to nx.

[0060] The λ / 2 section 41 has two delay elements (first delay elements) Q and two delay elements (second delay elements) ZA. The λ / 2 section 41 is a laminate in which the two delay elements Q and the two delay elements ZA are laminated in the order of the delay element Q, the delay element ZA, the delay element ZA, and the delay element Q, as shown in FIG.

[0061] [Delay element Q] The retarder element Q is a retardation film having reverse dispersion and imparting an in-plane retardation of approximately λ / 4 to the incident light of wavelength λ. Approximately λ / 4 means a range of 1 / 6 to 1 / 3 of the wavelength λ. The retarder element Q may be a λ / 4 plate. The retarder element Q may be a positive A plate having an in-plane retardation of approximately λ / 4 at a wavelength of 550 nm. The retarder element Q may be obtained by curing a polymerizable liquid crystal compound, or by molding or further stretching a molten resin.

[0062] [Late phase element ZA] The retarder element ZA is a retardation film that imparts a thickness direction retardation to incident light. The retarder element ZA can be a positive C plate. The positive C plate refers to a positive C plate whose thickness direction retardation Reth(550) satisfies formula (14). -30nm≧Reth(550)≧-120nm ··· (14)

[0063] The suitable value range of Reth(550) of the retarder element ZA is preferably -100 nm or more and -40 nm or less, more preferably -90 nm or more and -50 nm or less. The retarder element ZA may be obtained by curing a polymerizable liquid crystal compound, or may be obtained by molding or further stretching a molten resin. It is desirable that the in-plane retardation ReoZA(550) of the retarder element ZA is substantially 0. "Substantially 0" indicates a range of 0 nm±5.

[0064] When the retarder element Q and the retarder element ZA are layers obtained by curing a polymerizable liquid crystal, the retarder element Q and the retarder element ZA are formed on an alignment film provided on a substrate. The substrate may be a substrate having a function of supporting the alignment film and formed in a long length. This substrate functions as a releasable support and can support a retardation film for transfer. Furthermore, it is preferable that the surface of the substrate has an adhesive strength sufficient to allow peeling. As the substrate, the resin film exemplified as the material of the protective film 32 can be used.

[0065] The thickness of the substrate is not particularly limited, but is preferably in the range of 20 μm to 200 μm. When the thickness of the substrate is 20 μm or more, strength is imparted. On the other hand, when the thickness is 200 μm or less, an increase in processing waste and wear of the cutting blade can be suppressed when the substrate is cut into sheets of substrate.

[0066] The substrate may be subjected to various anti-blocking treatments. Examples of the anti-blocking treatment include an easy-adhesion treatment, a treatment for kneading a filler or the like, and an embossing (knurling) treatment. By subjecting the substrate to such an anti-blocking treatment, it is possible to effectively prevent the substrates from sticking to each other when the substrates are wound up, that is, so-called blocking, and it is possible to produce an optical film with high productivity.

[0067] The layer of the cured polymerizable liquid crystal compound is formed on the substrate via the alignment film. That is, the substrate and the alignment film are laminated in this order, and the layer of the cured polymerizable liquid crystal compound is laminated on the alignment film.

[0068] The alignment film is not limited to a vertical alignment film, and may be an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound horizontally, or an alignment film that aligns the molecular axis of the polymerizable liquid crystal compound at an inclination. When the retarder element Q is produced, a horizontal alignment film can be used, and when the retarder element ZA is produced, a vertical alignment film can be used.

[0069] The alignment film is preferably one that has solvent resistance such that it is not dissolved by coating of a composition containing a polymerizable liquid crystal compound described later, and also has heat resistance in a heat treatment for removing the solvent and orienting the liquid crystal compound. Examples of the alignment film include an alignment film containing an alignment polymer, a photoalignment film, and a groove alignment film that forms a concave-convex pattern or a plurality of grooves on the surface to provide alignment. The thickness of the alignment film is usually in the range of 10 nm to 10,000 nm, preferably in the range of 10 nm to 1000 nm, more preferably 500 nm or less, and further preferably in the range of 10 nm to 200 nm.

[0070] The resin used for the alignment film is not particularly limited as long as it is a resin used as a material for known alignment films, and a cured product obtained by curing a conventionally known monofunctional or polyfunctional (meth)acrylate monomer under a polymerization initiator, etc., can be used. Specifically, examples of the (meth)acrylate monomer include 2-ethylhexyl acrylate, cyclohexyl acrylate, diethylene glycol mono 2-ethylhexyl ether acrylate, diethylene glycol monophenyl ether acrylate, tetraethylene glycol monophenyl ether acrylate, trimethylolpropane triacrylate, lauryl acrylate, lauryl methacrylate, isobornyl acrylate, isobornyl methacrylate, 2-phenoxyethyl acrylate, tetrahydrofurfuryl acrylate, 2-hydroxypropyl acrylate, benzyl acrylate, tetrahydrofurfuryl methacrylate, 2-hydroxyethyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, methacrylic acid, and urethane acrylate. The resin may be one of these, or a mixture of two or more of them.

[0071] The type of polymerizable liquid crystal compound used in this embodiment is not particularly limited, but can be classified into rod-shaped type (rod-shaped liquid crystal compound) and discotic type (discotic liquid crystal compound) based on their shape. Each type can be further classified into low molecular type and high molecular type. Note that a high molecular weight generally refers to a material with a degree of polymerization of 100 or more (Polymer Physics: Phase Transition Dynamics, Masao Doi, p. 2, Iwanami Shoten, 1992).

[0072] In this embodiment, any of the polymerizable liquid crystal compounds may be used. Furthermore, two or more kinds of rod-shaped liquid crystal compounds, two or more kinds of discotic liquid crystal compounds, or a mixture of rod-shaped and discotic liquid crystal compounds may be used.

[0073] As the rod-shaped liquid crystal compound, for example, those described in claim 1 of JP-T-11-513019 or those described in paragraphs

[0026] to

[0098] of JP-A-2005-289980 can be preferably used. As the discotic liquid crystal compound, for example, those described in paragraphs

[0020] to

[0067] of JP-A-2007-108732 or those described in paragraphs

[0013] to

[0108] of JP-A-2010-244038 can be preferably used.

[0074] Two or more kinds of polymerizable liquid crystal compounds may be used in combination. In this case, at least one kind has two or more polymerizable groups in the molecule. That is, the layer in which the polymerizable liquid crystal compound is cured is preferably a layer formed by fixing a liquid crystal compound having a polymerizable group by polymerization. In this case, it is no longer necessary to show liquid crystallinity after the layer is formed.

[0075] The polymerizable liquid crystal compound has a polymerizable group capable of undergoing a polymerization reaction. As the polymerizable group, for example, a functional group capable of an addition polymerization reaction, such as a polymerizable ethylenically unsaturated group or a ring-polymerizable group, is preferable. More specifically, as the polymerizable group, for example, a (meth)acryloyl group, a vinyl group, a styryl group, an allyl group, etc. can be mentioned. Among them, a (meth)acryloyl group is preferable. Note that the (meth)acryloyl group is a concept that includes both a methacryloyl group and an acryloyl group.

[0076] The layer in which the polymerizable liquid crystal compound is cured can be formed by, for example, applying a composition containing the polymerizable liquid crystal compound onto an alignment film. The composition may contain components other than the above-mentioned polymerizable liquid crystal compound. For example, the composition preferably contains a polymerization initiator. The polymerization initiator used is, for example, a thermal polymerization initiator or a photopolymerization initiator, selected according to the type of polymerization reaction. For example, the photopolymerization initiator may be an α-carbonyl compound, an acyloin ether, an α-hydrocarbon-substituted aromatic acyloin compound, a polynuclear quinone compound, or a combination of a triaryl imidazole dimer and p-aminophenyl ketone. The amount of the polymerization initiator used is preferably 0.01% by mass to 20% by mass, more preferably 0.5% by mass to 5% by mass, based on the total solid content in the coating liquid.

[0077] The composition may contain a polymerizable monomer from the viewpoint of uniformity of the coating film and strength of the film. The polymerizable monomer may be a radically polymerizable or cationic polymerizable compound. Among them, a polyfunctional radically polymerizable monomer is preferable.

[0078] The polymerizable monomer is preferably one that can be copolymerized with the above-mentioned polymerizable liquid crystal compound.Specific examples of the polymerizable monomer include those described in paragraphs

[0018] to

[0020] of JP-A-2002-296423.The amount of the polymerizable monomer used is preferably 1 to 50% by mass, more preferably 2 to 30% by mass, based on the total mass of the polymerizable liquid crystal compound.

[0079] The composition may contain a surfactant from the viewpoint of uniformity of the coating film and strength of the film. Examples of the surfactant include conventionally known compounds. Among them, fluorine-based compounds are particularly preferred. Specific examples of the surfactant include the compounds described in paragraphs

[0028] to

[0056] of JP-A-2001-330725 and the compounds described in paragraphs

[0069] to

[0126] of JP-A-2003-295212.

[0080] The composition may contain a solvent, and an organic solvent is preferably used. Examples of the organic solvent include amides (e.g., N,N-dimethylformamide), sulfoxides (e.g., dimethyl sulfoxide), heterocyclic compounds (e.g., pyridine), hydrocarbons (e.g., benzene, hexane), alkyl halides (e.g., chloroform, dichloromethane), esters (e.g., methyl acetate, ethyl acetate, butyl acetate), ketones (e.g., acetone, methyl ethyl ketone), and ethers (e.g., tetrahydrofuran, 1,2-dimethoxyethane). Among these, alkyl halides and ketones are preferred. Two or more organic solvents may be used in combination.

[0081] The composition may contain various alignment agents, such as a vertical alignment promoter such as a polarizing film interface side vertical alignment agent and an air interface side vertical alignment agent, and a horizontal alignment promoter such as a polarizing film interface side horizontal alignment agent and an air interface side horizontal alignment agent. Furthermore, the composition may contain an adhesion improver, a plasticizer, a polymer, etc., in addition to the above components.

[0082] The direction of the slow axis of the slow retarder element Q in the λ / 2 portion 41 may be substantially aligned with the direction of the slow axis 41a in the λ / 2 portion 41. "Substantially aligned" means that the directions of the two slow axes may be shifted by about ±5° (hereinafter the same).

[0083] The retardation element Q in the λ / 2 portion 41 may be a laminate of a plurality of retardation films that function as the retardation element Q as a whole. The directions of the slow axes of the retardation films that constitute the retardation element Q are approximately the same as the direction of the slow axis 41a. Similarly, the retardation element Z in the λ / 2 portion 41 may be a laminate of a plurality of retardation films that function as the retardation element Z as a whole.

[0084] The λ / 4 section 42 has a delay phase element Q. The delay phase element Q of the λ / 4 section 42 has the same characteristics as the delay phase element Q of the λ / 2 section 41, so a description thereof will be omitted. The λ / 4 section 42 may have a delay phase element (third delay phase element) ZB. In this case, the λ / 4 section 42 is a laminate in which the delay phase element Q and the delay phase element ZB are laminated in this order from the λ / 2 section 41 side. Unless otherwise specified, a form in which the λ / 4 section 42 has the delay phase element ZB will be described. The slow axis of the delay phase element Q of the λ / 4 section 42 corresponds to the slow axis of the λ / 4 section 42. Therefore, the retardation element Q of the λ / 4 section 42 is disposed with respect to the λ / 2 section 41 such that the angle between its retardation axis and the retardation axis 41a of the λ / 2 section 41 is approximately 60°.

[0085] [Lagging element ZB] The retarder element ZB is a retardation film that imparts a thickness direction retardation to the incident light of wavelength λ. The retarder element ZB is a positive C plate or a negative C plate. The range of the thickness direction retardation RethZB(550) at a wavelength of 550 nm is usually from −190 nm to less than 0, and from more than 0 to +40 nm, preferably from −170 nm to less than 0 nm. The in-plane retardation ReoZB(550) is preferably substantially 0. Substantially 0 indicates a range of 0 nm±5. As in the case of the retarder element ZA, the retarder element ZB may be obtained by curing a polymerizable liquid crystal, or may be obtained by molding or further stretching a molten resin. When the retarder element ZB is a layer obtained by curing a polymerizable liquid crystal, the retarder element ZB may be formed on an alignment film provided on a substrate as in the case of the retarder element Z.

[0086] The retardation element Q in the λ / 4 section 42 may be a laminate of a plurality of retardation films that function as the retardation element Q as a whole. The directions of the slow axes of the retardation films that constitute the retardation element Q are approximately the same as the direction of the slow axis 42a. Similarly, the retardation element ZB in the λ / 4 section 42 may be a laminate of a plurality of retardation films that function as the retardation element ZB as a whole.

[0087] The conditions that the display device 100 must satisfy will be further explained.

[0088] [ρ coefficient] As shown in Fig. 3, a plane perpendicular to the direction D2 of the inclination angle α with respect to the thickness direction D1 of the image display layer 10 is called a projection plane VP. The in-plane retardation of the image display layer 10 at a wavelength of 550 nm on the projection plane VP when the inclination angle α is 45° is defined as ReM45. The in-plane retardation of the λ / 4 portion 42 is defined as ReoQ. In this embodiment, ReoQ corresponds to the in-plane retardation of the retarder element Q. In this case, the ρ coefficient is defined by formula (A). ρ=ReM45 / ReoQ (A)

[0089] When the ρ coefficient is defined by formula (A), the Nz coefficient of the λ / 4 unit 42 and the ρ coefficient satisfy the relationship shown in formula (B) in the display device 100. In other words, the λ / 4 unit 42 is designed so that the Nz coefficient satisfies formula (B). 4.5ρ-0.160 <Nz<4.5ρ+0.955 ···(B)

[0090] The Nz coefficient of the λ / 4 portion 42 in the formula (B) is defined by the following formula (C). Nz={(RethQ+RethZB) / (ReoQ+ReoZB)}+0.5···(C) In the formula (C), ReoQ is the in-plane retardation of the retarder element Q of the λ / 4 portion 42, as described above, and ReoZB is the in-plane retardation of the retarder element ZB of the λ / 4 portion 42. In formula (C), RethQ is the thickness direction retardation of the retarder element Q of the λ / 4 portion 42, and RethZB is the thickness direction retardation of the retarder element ZB of the λ / 4 portion 42.

[0091] In formula (B), when the value of the ρ coefficient is in the range of -0.06 or more and -0.02 or less, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of more than -0.43 and less than 0.87. In formula (B), when the value of the ρ coefficient is in the range of −0.02 or more and less than 0, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of more than −0.25 and less than 0.96. In formula (B), when the value of the ρ coefficient is in the range of more than 0 and not more than 0.04, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of more than -0.16 and less than 1.14. In formula (B), when the value of the ρ coefficient is in the range of more than 0.04 and less than 0.08, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of more than 0.02 and less than 1.32.

[0092] It is more preferable that the relationship between the Nz coefficient and the ρ coefficient of the λ / 4 portion 42 satisfy the relationship shown in formula (D). 4.5ρ-0.035≦Nz≦4.5ρ+0.690 (D)

[0093] In formula (D), when the value of the ρ coefficient is in the range of −0.06 or more and −0.02 or less, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of −0.31 or more and 0.60 or less. In formula (D), when the value of the ρ coefficient is in the range of −0.02 or more and less than 0, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of −0.13 or more and less than 0.69. In formula (D), when the value of the ρ coefficient is in the range of more than 0 and not exceeding 0.04, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of more than -0.04 and not exceeding 0.87. In formula (D), when the value of the ρ coefficient is in the range of 0.04 to 0.08, the value of the Nz coefficient of the λ / 4 portion 42 is in the range of 0.15 to 1.05.

[0094] The linear polarizer 30, the optical laminate 40, and the members constituting the display device 100 (including the retarder element Q, the retarder element ZA, and the retarder element ZB) can be laminated using, for example, an adhesive layer (not shown). When the image display layer 10 includes an electrode of the organic EL display element, the organic EL display element and the optical laminate 40 may be laminated via an adhesive layer.

[0095] The adhesive layer can be composed of an adhesive composition mainly composed of a resin such as a (meth)acrylic, rubber, urethane, ester, silicone, or polyvinyl ether resin. Among them, an adhesive composition having a (meth)acrylic resin as a base polymer, which is excellent in transparency, weather resistance, heat resistance, etc., is preferable. The adhesive composition may be an active energy ray curable type or a heat curable type. The thickness of the adhesive layer is usually 3 μm to 30 μm, and preferably 3 μm to 25 μm.

[0096] As the (meth)acrylic resin (base polymer) used in the pressure-sensitive adhesive composition, for example, a polymer or copolymer containing one or more (meth)acrylic acid esters as monomers, such as butyl (meth)acrylate, ethyl (meth)acrylate, isooctyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, is preferably used. It is preferable to copolymerize a polar monomer into the base polymer. Examples of the polar monomer include monomers having a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, and the like, such as (meth)acrylic acid, 2-hydroxypropyl (meth)acrylate, hydroxyethyl (meth)acrylate, (meth)acrylamide, N,N-dimethylaminoethyl (meth)acrylate, and glycidyl (meth)acrylate.

[0097] The adhesive composition may contain only the base polymer, but usually further contains a crosslinking agent. Examples of the crosslinking agent include divalent or higher metal ions that form a carboxylate metal salt with a carboxyl group; polyamine compounds that form an amide bond with a carboxyl group; polyepoxy compounds or polyols that form an ester bond with a carboxyl group; and polyisocyanate compounds that form an amide bond with a carboxyl group. Among them, polyisocyanate compounds are preferred.

[0098] [Method of manufacturing an elliptically polarizing plate and a display device] The elliptical polarizing plate 20 is manufactured by laminating the optical laminate 40 including the λ / 2 portion 41 and the λ / 4 portion 42 and the polarizer 31 via an adhesive layer. For example, as shown in FIG. 1, when using a linear polarizing plate 30 in which a protective film 32 is laminated on both sides of the polarizer 31, the polarizer 31 is manufactured and the protective film 32 is laminated on both sides of the polarizer 31 to obtain the linear polarizing plate 30. Thereafter, an adhesive layer formed on a release film is laminated on the protective film 32 facing the optical laminate 40. The release film on the adhesive layer is peeled off, and the polarizer 31 and the λ / 2 portion 41 and the λ / 4 portion 42, which are separately manufactured, are bonded together via the exposed adhesive layer to obtain the elliptical polarizing plate 20. The elliptical polarizing plate 20 is laminated on the image display layer 10 via an adhesive layer, for example, to obtain the display device 100.

[0099] The display device 100 satisfies formula (A) and formula (B). In this case, the λ / 4 portion 42 of the elliptical polarizer 20 is designed in consideration of the light reflectivity of the image display layer 10 in the direction of the tilt angle of 45°. Therefore, even when the display device 100 is tilted, external light reflection is prevented, and good display performance can be realized. With the configuration of the display device 100, the above-mentioned good display performance can be realized over the entire visible range.

[0100] The present invention is not limited to the above-described embodiments, but is intended to include the scope indicated by the claims, and to include all modifications within the meaning and scope equivalent to the claims. EXAMPLES

[0101] The present invention will be specifically described below with reference to examples. In the following description, "%" and "parts" mean mass% and mass parts unless otherwise specified. The present invention is not limited to the following examples. In the following description, a positive C plate that can be used for both the retarder element ZA and the retarder element ZB may be referred to as the retarder element Z.

[0102] [Measurement method] ·How to measure film thickness The film thickness was measured using a contact type film thickness meter ("MH-15M", "Counter TC101", "MS-5C", manufactured by Nikon Corporation).

[0103] How to measure retardation The retardation in the thickness direction of the λ / 2 and λ / 4 parts, and the in-plane retardation of the λ / 2, λ / 4 and elliptical polarizers were measured using a retardation measuring device ("KOBRA-WPR", manufactured by Oji Scientific Instruments Co., Ltd.).

[0104] How to measure the refractive index The refractive index of the film, layer, etc. was measured using a spectroscopic ellipsometer ("M-2000", manufactured by JA Woollam).

[0105] Visibility correction and hue calculation method The luminosity-corrected single transmittance Ty, single transmission hue a, single transmission hue b, and luminosity-corrected polarization degree Py, as well as the luminosity-corrected reflectance Ry10 and luminosity-corrected reflectance Ry45, which will be described later, were calculated using the corresponding spectral spectra, i.e., the single spectral transmittance T, the spectral polarization degree P, the spectral reflectance R, and the color matching functions and standard illuminant.

[0106] The luminosity correction value is obtained by dividing the tristimulus value Y of the corresponding spectral spectrum by the tristimulus value Yo of the standard illuminant. Hues a and b are the hues in the Lab color system of the corresponding spectral spectrum (see "Introduction to Color Engineering," Hiroyuki Shinoda and Ichiro Fujieda, Morikita Publishing, pp. 106-107, 2007). The color matching function used was that recommended by the International Commission on Illumination (CIE) (1931). The standard illuminant used was D65 (ISO10526:1999 / CIES005 / E-1998).

[0107] Measurement method for the spectral polarization degree P, single spectral transmittance T, and single transmittance hue a, b of a polarizer The spectral transmittance in the transmission axis direction and the spectral transmittance in the absorption axis direction of the polarizer were measured using an ultraviolet-visible spectrophotometer ("V7100", manufactured by JASCO Corporation), and the spectral polarization degree P, the single spectral transmittance T, the single transmission hue a, and the single transmission hue b were calculated.

[0108] The single-piece spectral transmittance T is the average value of the transmission axial direction spectral transmittance and the absorption axial direction spectral transmittance. The degree of spectral polarization P is obtained by dividing the difference between the spectral transmittance in the transmission axis direction and the spectral transmittance in the absorption axis direction by the sum of the spectral transmittance in the transmission axis direction and the spectral transmittance in the absorption axis direction. The spectral transmittance in the transmission axis direction is the transmittance at each wavelength for linearly polarized light that vibrates parallel to the transmission axis of the polarizer. The spectral transmittance in the absorption axis direction is the transmittance at each wavelength for linearly polarized light that vibrates parallel to the absorption axis of the polarizer.

[0109] The absorption axis of the polarizer coincided with the stretching direction of the polyvinyl alcohol.

[0110] -Measurement of reflectance and reflected hue The spectral reflectance R was measured using the SCI mode of a display measurement system ("DMS803", manufactured by Instrument Systems) when an elliptically polarizing plate was placed on the light reflecting layer, and the luminosity-corrected reflectance Ry was calculated.

[0111] The spectral reflectance R was measured at tilt angles θ = 10° and θ = 45° (the tilt angles are described later), with the reflection intensity of only the light-reflecting layer without the elliptically polarizing plate being taken as 100%. The measurement wavelengths were in the range of 380 nm to 780 nm in 1 nm increments.

[0112] The direction perpendicular to the plane (hereinafter, for convenience of explanation, referred to as "plane p") that is spanned by an axis parallel to the refractive index nx and an axis parallel to the refractive index ny (corresponding to direction D1 shown in FIG. 3) is set to an inclination angle θ=0°. With the in-plane angle φ in plane p as the central axis of inclination, the spectral reflectance R was measured for each of the inclination angles θ of 10° and 45° in the range of equation (15) in 5° steps. Plane p corresponds to the surfaces of retarder elements Q, ZA, and ZB, the surface of an elliptical polarizer, etc., and is also a surface parallel to image display surface 10a. 0°≦φ<360° (15)

[0113] The average value of the in-plane angle region of the visibility-corrected reflectance at a tilt angle θ = 10° (the angle range shown in formula (15), the same applies below) was defined as Ry10. The average value of the in-plane angle region of the visibility-corrected reflectance at a tilt angle θ = 45° was defined as Ry45.

[0114] [Preparation of composition for forming horizontal alignment film] 5 parts of a photoalignment material (weight average molecular weight: 30,000) having the following structure was mixed with 95 parts of cyclopentanone (solvent). The resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a horizontal alignment film. [ka]

[0115] [Preparation of composition for forming vertical alignment film] Sunever SE610 manufactured by Nissan Chemical Industries, Ltd. was used.

[0116] [Preparation of Composition for Forming Retardation Element Q] To form retarder element Q (reverse dispersion positive A plate), the following polymerizable liquid crystal compound A and polymerizable liquid crystal compound B were used. Polymerizable liquid crystal compound A was produced by the method described in JP-A-2010-31223. Polymerizable liquid crystal compound B was produced according to the method described in JP-A-2009-173893. The molecular structures of each are shown below.

[0117] [Polymerizable liquid crystal compound A] [ka]

[0118] [Polymerizable liquid crystal compound B] [ka]

[0119] Polymerizable liquid crystal compound A and polymerizable liquid crystal compound B were mixed in a mass ratio of 90:10. 1.0 part of a leveling agent ("Megafac F-556", manufactured by DIC Corporation) and 6 parts of a polymerization initiator, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one ("Omnirad369", manufactured by IGM Resins BV), were added to 100 parts of the obtained mixture. Furthermore, N-methyl-2-pyrrolidone (NMP) was added so that the solid content concentration was 13%, and the mixture was stirred at 80°C for 1 hour to obtain a composition for forming retarder element Q.

[0120] [Preparation of composition for forming retarder element Z] To form a retarder element Z (positive C plate), a composition was prepared by the following procedure. 0.1 parts of F-556 as a leveling agent and 3 parts of Omnirad369 as a polymerization initiator were added to 100 parts of a polymerizable liquid crystal compound ("Paliocolor LC242", manufactured by BASF). Cyclopentanone was added so that the solid content concentration became 13%, and a composition for forming retarder element Z was obtained.

[0121] [Preparation of Polarizer] A polyvinyl alcohol (PVA) film with an average degree of polymerization of about 2,400, a degree of saponification of 99.9 mol% or more, and a thickness of 75 μm was prepared. The PVA film was immersed in pure water at 30°C, and then immersed in an aqueous solution with a mass ratio of iodine / potassium iodide / water of 0.02 / 2 / 100 at 30°C to perform iodine dyeing (iodine dyeing process). The PVA film that had undergone the iodine dyeing process was immersed in an aqueous solution with a mass ratio of potassium iodide / boric acid / water of 12 / 5 / 100 at 56.5°C to perform boric acid treatment (boric acid treatment process). The PVA film that had undergone the boric acid treatment process was washed with pure water at 8°C, and then dried at 65°C to obtain a polarizing film in which iodine was adsorbed and aligned in the polyvinyl alcohol. The PVA film was stretched in the iodine dyeing process and the boric acid treatment process. The total stretching ratio of the PVA film was 5.3 times. The resulting polarizing film had a thickness of 10 μm.

[0122] The polarizing film and a saponified triacetyl cellulose (TAC) film (KC4UYTAC, 40 μm thick, manufactured by Konica Minolta, Inc.) were bonded together by nip rolls via a water-based adhesive. The resulting laminate was dried at 60° C. for 2 minutes while maintaining the tension at 430 N / m to obtain a polarizer having a TAC film as a protective film on one side. The water-based adhesive was prepared by adding 3 parts of carboxyl-modified polyvinyl alcohol (Kuraray Co., Ltd., "Kuraray Poval KL318") and 1.5 parts of water-soluble polyamide epoxy resin (Taoka Chemical Co., Ltd., "Sumirase Resin 650", an aqueous solution with a solid content of 30%) to 100 parts of water.

[0123] The optical properties of the obtained polarizer were measured. The luminous efficiency-corrected single transmittance Ty of the obtained polarizer was 41.9%, the luminous efficiency-corrected polarization degree Py of the obtained polarizer was 99.962%, the single transmission hue a of the polarizer was -1.5, and the single transmission hue b of the polarizer was 3.6.

[0124] [Preparation of retarder element Q (reverse dispersion positive A plate)] Corona treatment was carried out on a cyclic olefin resin (COP) film (ZF-14-50) manufactured by Zeon Corporation. The corona treatment was carried out using a TEC-4AX manufactured by Ushio Inc. The corona treatment was carried out once under the conditions of an output of 0.78 kW and a treatment speed of 10 m / min. The composition for forming a horizontal alignment film was applied to the COP film using a bar coater and dried at 80°C for 1 minute. A polarized UV irradiation device ("SPOT CURE SP-9", manufactured by Ushio Inc.) was used to irradiate the applied film with an integrated light amount of 100 mJ / cm at a wavelength of 313 nm. 2 Polarized UV exposure was performed at an axial angle of 45° so that the thickness of the obtained horizontal alignment film was 100 nm.

[0125] Next, a composition for forming a retarder element Q (reverse dispersion positive A plate) was applied to the horizontal alignment film using a bar coater and dried for 1 minute at 120° C. The applied film was irradiated with ultraviolet light (accumulated light amount at a wavelength of 365 nm under a nitrogen atmosphere: 500 mJ / cm ) using a high-pressure mercury lamp ("Uniquer VB-15201BY-A", manufactured by Ushio Inc.). 2 ) to form the retarder element Q. The retarder element Q had a film thickness of 2.3 μm.

[0126] A film formed by a COP film, an alignment film, and a horizontally aligned liquid crystal cured film was attached to glass via an adhesive layer on the retarder element Q. The COP film was peeled off to obtain a sample for measuring retardation. The in-plane retardation ReoQ(λ) of the retarder element Q at each wavelength was measured, and the results were as follows: ReoQ(450)=121 nm, ReoQ(550)=142 nm, ReoQ(650)=146 nm, ReoQ(450) / ReoQ(550)=0.85, ReoQ(650) / ReoQ(550)=1.03, and the retarder element Q exhibited inverse wavelength dispersion.

[0127] The retardation element Q was a positive A plate that satisfied the relationship nx>ny≒nz. The thickness direction retardation RethQ(λ) was measured at each wavelength, and the results were as follows: RethQ(450)=61 nm, RethQ(550)=72 nm, RethQ(650)=73 nm, It was.

[0128] [Fabrication of retarder element Z (positive C plate)] The COP film was subjected to a corona treatment. The corona treatment conditions were the same as those described above. The composition for forming a vertical alignment film was applied onto the COP film using a bar coater and dried at 80°C for 1 minute to obtain a vertical alignment film. The thickness of the obtained vertical alignment film was 50 nm.

[0129] The composition for forming the retarder element Z was applied to the vertical alignment film using a bar coater and dried at 90 °C for 120 seconds. The coated film was irradiated with ultraviolet light (under a nitrogen atmosphere, integrated light amount at a wavelength of 365 nm: 500 mJ / cm 2 ) to form the retarder element Z. In this way, a film formed by the COP film, the vertical alignment film, and the retarder element Z was obtained. The film thickness of the retarder element Z was 0.6 μm.

[0130] An adhesive layer was laminated on the retarder element Z. Through the adhesive layer, the film formed by the COP film, the alignment film, and the retarder element Z was bonded to glass. The COP film was peeled off to obtain a sample for measuring retardation. As a result of measuring the thickness-direction retardation RethZ(550) of the retarder element Z at a wavelength of 550 nm, RethZ(550) = -70 nm, it was. As a result of measuring the in-plane retardation ReoZ(550) of the retarder element Z at a wavelength of 550 nm, ReoZ(550) = 0.1 nm, and the in-plane retardation of the retarder element Z was substantially 0. The retarder element Z was a positive C-plate satisfying the relation of nx ≒ ny < nz.

[0131] <Fabrication of Negative C-Plate> Two TAC films (「Fujitac TG60UL」, manufactured by Fujifilm) with a thickness of 60 μm were adhered via an adhesive layer to obtain a TAC film laminate formed by the TAC film, the adhesive, and the TAC film. Next, the TAC film laminate was bonded to glass via an adhesive layer to obtain a sample for measuring retardation. As a result of measuring the thickness-direction retardation Reth(550) at a wavelength of 550 nm, Reth(550) = +40 nm, It was. The TAC film laminate was a negative C plate that satisfied the relationship of nx≒ny>nz. Therefore, the in-plane retardation of the TAC film laminate was set to be substantially zero.

[0132] [Layer laminate 1] The vertical alignment film and the delay phase element Z in the delay phase element Z formed on the COP film, and the horizontal alignment film and the delay phase element Q in the delay phase element Q formed on the COP film were bonded together via an adhesive, and then the COP film on the delay phase element Z side was peeled off to obtain a film in which the COP film and the delay phase laminate 1 were laminated in this order. The arrangement relationship of the delay phase element Q and the delay phase element Z in the delay phase laminate 1 was as follows. The delay phase element Z of the delay phase laminate 1 was a positive C plate. In order to show the arrangement of the delay phase element Q and the delay phase element Z relative to the COP film, the COP film is shown in parentheses in the following arrangement relationship. Therefore, the following notation indicates that the delay phase element Z and the delay phase element Q are arranged in the order of the delay phase element Q and the delay phase element Z from the COP film side. A similar notation may be adopted for the arrangement relationship between elements (or layers). (COP film) / Q / Z

[0133] [Layer laminate 2] The vertical alignment film and the lagging phase element Z in the lagging phase element Z formed on the COP film, and the horizontal alignment film and the lagging phase element Q in the lagging phase element Q formed on the COP film were bonded via an adhesive, and then the COP film on the lagging phase element Q side was peeled off to obtain a film in which the COP film and the lagging phase laminate 2 were laminated in this order. The positional relationship between the lagging phase element Q and the lagging phase element Z in the lagging phase laminate 2 was as follows. The lagging phase element Z of the lagging phase laminate 2 was a positive C plate. (COP film) / Z / Q

[0134] [Layer laminate 3] The above TAC film laminate was bonded to the horizontal alignment film formed on the COP film and the retarder element Q in the retarder element Q via an adhesive, and then the COP film on the retarder element Q side was peeled off to obtain a retarder laminate 3. The TAC film laminate was a negative C plate. Therefore, the retarder laminate 3 was a laminate of the retarder element ZB, which was a negative C plate, and the retarder element Q.

[0135] <Elliptical polarizing plate EP1> ·λ / 2 part Two films formed of a COP film and a delay laminate 1, cut so that the delay axes of the two layers of delay phase elements Q are in the same direction when the delay phase elements Z sides are in contact with each other, are prepared, and the delay phase elements Z sides of each film are bonded via an adhesive. Then, the COP film on one of the delay phase elements Q sides is peeled off to obtain a film in which the COP film, λ / 2 part (lagging phase element Q, adhesive layer, delay phase element Z, adhesive layer, delay phase element Z, adhesive layer, delay phase element Q) are laminated in this order. Note that the λ / 2 part (lagging phase element Q, adhesive layer, delay phase element Z, adhesive layer, delay phase element Z, adhesive layer, delay phase element Q) means that in the λ / 2 part, the delay phase element Q, adhesive layer, delay phase element Z, adhesive layer, delay phase element Z, adhesive layer, delay phase element Q, adhesive layer, delay phase element Q are arranged in this order. Similar notations may be adopted for other members (for example, λ / 4 part). The retardation element Z in the λ / 2 portion is a positive C plate because it is the retardation element Z in the retarder laminate 1. Therefore, since the retardation element Z in the λ / 2 portion is the retardation element ZA, hereinafter the retardation element Z of the elliptical polarizer EP1 will be referred to as the retardation element ZA.

[0136] ·λ / 4 part The retardation laminate 2 having the retardation element Z manufactured by adjusting the thickness direction retardation to be RethZ(550)=-70 nm was defined as the λ / 4 part. Hereinafter, when the retardation laminate 2 is used in the λ / 4 part, the retardation element Z of the retardation laminate 2 is referred to as the retardation element ZB, and the thickness direction retardation at a wavelength of 550 nm is referred to as RethZB(550).

[0137] Elliptical polarizer EP1 In the polarizer having the TAC film laminated thereon, the surface opposite to the TAC film was bonded to the retarder element Q side of the film formed of the COP film and the λ / 2 part via an adhesive layer, and the COP film was peeled off to obtain a laminate. At this time, the angle between the transmission axis of the polarizer and the retarder element Q side of the λ / 2 part was 15°. Next, the retarder element Q side of the laminate was bonded to the retarder element Q side of the film formed of the COP film and the λ / 4 part via an adhesive layer, and the COP film was peeled off to obtain an elliptical polarizing plate EP1. At this time, the angle between the transmission axis of the polarizer and the retarder axis of the λ / 4 part was 75°. The Nz coefficient of the λ / 2 part was 0.51, and the Nz coefficient of the λ / 4 part was 0.51.

[0138] The elliptical polarizing plate EP1 had a layer structure of a TAC film, a polarizer, an adhesive layer, a λ / 2 part (lagging element Q, adhesive layer, lagging element ZA, adhesive layer, lagging element ZA, adhesive layer, lagging element Q), an adhesive layer, a λ / 4 part (lagging element Q, adhesive layer, lagging element ZB).

[0139] <Elliptical polarizing plate EP2> An elliptical polarizing plate EP2 was obtained in the same manner as the elliptical polarizing plate EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to be RethZB(550)=-30 nm was used as the λ / 4 portion. N Z The coefficient was 0.79.

[0140] <Elliptical polarizing plate EP3> An elliptical polarizer EP3 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to be RethZB(550)=-100 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was 0.30.

[0141] <Elliptical polarizing plate EP4> An elliptical polarizer EP4 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to RethZB(550)=-170 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was -0.20.

[0142] <Elliptical polarizing plate EP5> An elliptical polarizer EP5 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to be RethZB(550)=-190 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was -0.34.

[0143] <Elliptical polarizing plate EP6> An elliptical polarizer EP6 was obtained in the same manner as the elliptical polarizer EP1, except that it did not contain the retarder element ZB. The Nz coefficient at the λ / 4 portion was 1.00.

[0144] <Elliptical polarizing plate EP7> An elliptical polarizer EP7 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to be RethZB(550)=-40 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was 0.72.

[0145] <Elliptical polarizing plate EP8> An elliptical polarizer EP8 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to RethZB(550)=-140 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was 0.01.

[0146] <Elliptical polarizing plate EP9> An elliptical polarizer EP9 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to RethZB(550)=-160 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was -0.13.

[0147] <Elliptical polarizing plate EP10> In the polarizer laminated with the TAC film, the surface opposite to the TAC film was bonded to the retarder element Q side of the film formed of the COP film and the λ / 2 part via an adhesive layer, and the COP film was peeled off to obtain a laminate. At this time, the angle between the transmission axis of the polarizer and the slow axis of the λ / 2 part was 15°. Next, the retarder element Q side of the above laminate was bonded to the retarder element Q side of the retarder laminate 3 via an adhesive layer to obtain an elliptical polarizing plate EP10. At this time, the angle between the transmission axis of the polarizer and the slow axis of the λ / 4 part was 75°. At this time, the Nz coefficient of the λ / 2 part was 0.51, and the Nz coefficient of the λ / 4 part was 1.28.

[0148] <Elliptical polarizing plate EP11> An elliptical polarizer EP11 was obtained in the same manner as the elliptical polarizer EP1, except that the retardation laminate 2 having the retardation element ZB (retardation element Z) obtained by adjusting the thickness direction retardation to be RethZB(550)=-120 nm was used as the λ / 4 portion. The Nz coefficient of the λ / 4 portion was 0.15.

[0149] [Preparation of light-reflecting layer] The following three types of light reflecting layers were used. Light-reflecting layer A: A commercially available smartphone equipped with a Samsung Electronics OLED display, the GALAXY Tab S 8.4 SC-03G, was disassembled, and the cover glass and elliptical polarizing plate were removed. Light-reflective layer B: A commercially available smartphone equipped with an OLED display device manufactured by Huawei Technologies, a Mate 30 Pro, was disassembled, and the cover glass and elliptical polarizing plate were removed before use. Light-reflecting layer C: A commercially available smartphone equipped with an OLED display device manufactured by Apple Inc., iPhone® X, was disassembled, and the cover glass and the elliptical polarizing plate were removed.

[0150] The in-plane retardation ReM45 of each light reflecting layer at a wavelength of 550 nm on the projection plane with an inclination angle of 45° (projection plane VP described with reference to FIG. 3) was as shown in Table 1. [Table 1]

[0151] <Retardation of elliptical polarizers EP1 to EP5, EP7 to EP11> An adhesive layer was laminated on the retarder element ZB of each of the elliptical polarizers EP1 to EP5 and EP7 to EP11. The elliptical polarizers EP1 to EP5 and EP7 to EP11 were attached to glass via the adhesive layer to obtain samples for measuring retardation. The in-plane retardation Reo(λ) of the elliptical polarizers EP1 to EP5 and EP7 to EP11 at each wavelength was measured, and the results were as follows: Reo(450)=112 nm, Reo(550)=138nm, Reo(650)=162 nm, Reo(450) / Reo(550)=0.81, Reo(650) / Reo(550)=1.17, It was.

[0152] <Retardation of elliptical polarizer EP6> An adhesive layer was laminated on the retarder element Q of the elliptical polarizer EP6, and the elliptical polarizer EP6 was attached to glass via the adhesive layer to obtain a sample for measuring retardation. The in-plane retardation Reo(λ) at each wavelength was measured, and the results were as follows: Reo(450)=112 nm, Reo(550)=138nm, Reo(650)=162 nm, Reo(450) / Reo(550)=0.81, Reo(650) / Reo(550)=1.17, It was.

[0153] <Visual confirmation of display performance> For the combinations of the prepared elliptically polarizing plates EP1 to EP11 and the light reflecting layers A, B, and C, the display performance of the elliptically polarizing plates EP1 to EP11 was visually confirmed as follows. (Visual inspection method) The test was carried out outdoors on a clear day by five observers. Observations were made over the entire range of in-plane angles shown in formula (15) for both tilt angles of 10° and 45°. If four or more of the five observers did not notice rainbow-colored reflected light from the light-reflecting layer, the display was evaluated as having good display performance with reflected light well prevented. In all other cases, the display was evaluated as having impaired display performance.

[0154] <Reflectance at an inclination angle of 10° when light reflective layer A is used> The luminosity-corrected reflectance of each of the samples obtained by bonding each of the elliptical polarizers EP1 to EP5 onto the light-reflecting layer A with an adhesive was measured and calculated at an inclination angle of θ=10°, and the result was Ry10=4.7% for all of them. Furthermore, when the reflected external light was observed at an inclination angle of θ=10°, it was confirmed that the reflected light was well prevented in all cases, providing good display performance.

[0155] <Reflectance at an inclination angle of 10° when light reflective layer B is used> The luminosity-corrected reflectance of the samples obtained by bonding each of the elliptical polarizers EP1, EP6 to EP9 onto the light-reflecting layer B with an adhesive was measured and calculated at an inclination angle of θ=10°, and all were found to be Ry10=4.6%. Furthermore, when the reflected external light was visually observed at an inclination angle of θ=10°, it was confirmed that in all cases the reflected light was well prevented, providing good display performance.

[0156] <Reflectance at an inclination angle of 10° when light reflective layer C is used> The luminosity-corrected reflectance of the samples obtained by bonding each of the elliptical polarizers EP2, EP3, EP6, EP10, and EP11 onto the light-reflecting layer C with an adhesive was measured and calculated at an inclination angle of θ=10°, and all were found to be Ry10=4.5%. Furthermore, when the reflected external light was visually observed at an inclination angle of θ=10°, it was confirmed that in all cases the reflected light was well prevented, providing good display performance.

[0157] (1) Examples 1 to 3 The elliptically polarizing plates EP1, EP3, and EP4 were each attached to the light-reflecting layer A via an adhesive to obtain samples, and the luminosity-corrected reflectance Ry45 at an inclination angle θ=45° was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that in all cases, reflected light was well prevented, providing good display performance.

[0158] (2) Examples 4 to 6 The luminosity-corrected reflectance Ry45 at an inclination angle θ=45° of the samples obtained by bonding each of the elliptical polarizers EP7, EP1, and EP8 onto the light-reflecting layer B with an adhesive was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that reflected light was well prevented in all cases, providing good display performance.

[0159] (3) Examples 7 to 9 The elliptically polarizing plates EP6, EP2, and EP3 were each attached to the light-reflecting layer C via an adhesive to obtain samples, and the luminosity-corrected reflectance Ry45 at an inclination angle θ=45° was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that in all cases, reflected light was well prevented, providing good display performance.

[0160] (4) Comparative Examples 1 and 2 The elliptically polarizing plates EP2 and EP5 were attached to the light-reflecting layer A via an adhesive to obtain samples, and the luminosity-corrected reflectance Ry45 at an inclination angle θ=45° was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that in both cases, strong rainbow-colored reflected light was visible, impairing the display performance.

[0161] (5) Comparative Examples 3 and 4 The elliptically polarizing plates EP6 and EP9 were attached to the light-reflecting layer B via an adhesive to obtain samples, and the luminosity-corrected reflectance Ry45 at an inclination angle θ=45° was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that in both cases, strong rainbow-colored reflected light was visible, impairing the display performance.

[0162] (6) Comparative Examples 5 and 6 The elliptically polarizing plates EP10 and EP11 were attached to the light-reflecting layer C via an adhesive to obtain samples, and the luminosity-corrected reflectance Ry45 at an inclination angle θ=45° was measured and calculated. The calculation results are shown in Figure 4. Furthermore, when the external light reflection of the light-reflecting layer at an inclination angle θ=45° was observed under sunlight, it was confirmed that in both cases, strong rainbow-colored reflected light was visible, impairing the display performance.

[0163] FIG. 4 is a table showing the results of Examples 1 to 9 and Comparative Examples 1 to 6. In the chart of FIG. 4, A, B, and C in the “Type” column in the “Light Reflecting Layer” column correspond to light reflecting layer A, light reflecting layer B, and light reflecting layer C. The ρ coefficient in the "light reflecting layer" column is a value calculated by substituting ReM45 of the light reflecting layers A, B, and C shown in Table 1 and the in-plane retardation ReoQ of the λ / 4 portion of the retarder element Q of the elliptical polarizing plates EP1 to EP11 combined with the light reflecting layers A, B, and C into formula (A). The "Nz coefficient" is a value calculated by substituting the in-plane retardation and the thickness direction retardation of the retarder element Q and the retarder element ZB in the λ / 4 portion into formula (C). In the "Visual observation at an inclination angle of 45°" column, "◯" indicates "good display performance with good prevention of reflected light," and "×" indicates "rainbow-colored reflected light is visible, impairing display performance," as described below.

[0164] From the results shown in FIG. 4, in Examples 1 to 9, the evaluation of "visual observation at an inclination angle of 45°" was "good". That is, in Examples 1 to 9, even when the display device obtained by laminating an elliptically polarizing plate on a light-reflecting layer was tilted under sunlight and the external light reflection of the light-reflecting layer was observed, the reflected light was well prevented and the display performance was good. On the other hand, in Comparative Examples 1 to 6, the evaluation of "visual observation at an inclination angle of 45°" was "x". That is, in Comparative Examples 1 to 6, when the display device obtained by laminating an elliptically polarizing plate on a light-reflecting layer was tilted under sunlight and the external light reflection of the light-reflecting layer was observed, the rainbow-colored reflected light was visible and the display performance was impaired. Note that sunlight includes the entire visible range, so the evaluation of the display performance corresponds to the evaluation of the entire visible range. FIG. 4 shows the results at an inclination angle of 45°, but as described above, the results at an inclination angle of 10° were similar to those at an inclination angle of 45°.

[0165] Figure 5 is a graph plotting the Nz coefficient against the ρ coefficient in Figure 4. The horizontal axis in Figure 5 represents the ρ coefficient, and the vertical axis represents the Nz coefficient. Lines L1, L2, L3, L4, and L5 in Figure 5 are lines expressed by the following formula. L1: Nz=4.5ρ+0.955 L2: Nz=4.5ρ-0.160 L3: Nz=4.5ρ+0.690 L4: Nz=4.5ρ-0.035 L5: Nz=4.5ρ+0.5

[0166] From the relationship between the lines L1 to L4 shown in FIG. 5 and the plot points of the examples and the comparative examples, in the examples 1 to 9, the relationship between the Nz coefficient and the ρ coefficient at the λ / 4 part satisfies the formula (B), while in the comparative examples 1 to 6, the relationship between the Nz coefficient and the ρ coefficient at the λ / 4 part does not satisfy the formula (B). Therefore, it can be understood that, by making the relationship between the Nz coefficient and the ρ coefficient at the λ / 4 part satisfy the formula (B), even when the external light reflection of the light reflecting layer is observed with the display device tilted, good display performance in which reflected light is well prevented in the entire visible range can be obtained. Furthermore, from the relationship between the lines L1 to L4 shown in FIG. 5 and the plot points of the examples and the comparative examples, it can be understood that it is preferable that the relationship between the Nz coefficient and the ρ coefficient at the λ / 4 part satisfies the formula (D).

[0167] From the results of Ry45 shown in FIG. 4, it can be understood that Ry is preferably 8.1% or less. [Explanation of symbols]

[0168] 20... elliptical polarizing plate, 31... polarizer, 41... λ / 2 portion, 42... λ / 4 portion, 100... display device, Q... retarder element (first retarder element), ZA... (second retarder element), ZB... retarder element (third retarder element).

Claims

1. a light-reflective image-displaying layer; an elliptically polarizing plate laminated on the image display surface of the light-reflective image display layer; Equipped with The elliptical polarizing plate has a polarizer, a λ / 2 portion and a λ / 4 portion, the polarizer, the λ / 2 portion, and the λ / 4 portion are arranged in this order from the light-reflective image display layer side, the λ / 4 portion, the λ / 2 portion, and the polarizer; the λ / 2 portion is a laminate in which a first delay phase element, a second delay phase element, a second delay phase element and a first delay phase element are laminated in the order of the first delay phase element, the second delay phase element, the second delay phase element and the first delay phase element, the first retardation element has a reverse wavelength dispersion and provides an in-plane retardation of approximately λ / 4; The second retardation element is an element that imparts a thickness direction retardation, When the in-plane retardation of the light reflective image display layer at a wavelength of 550 nm on a projection plane having an inclination angle of 45° with respect to the thickness direction of the light reflective image display layer is ReM45, the in-plane retardation of the λ / 4 part at a wavelength of 550 nm is ReoQ, and the ρ coefficient of the light reflective image display layer is expressed by formula (A), the Nz coefficient of the λ / 4 part and the ρ coefficient satisfy the relationship shown in formula (B). Display device. ρ=ReM45 / ReoQ...(A) 4.5ρ-0.160<Nz<4.5ρ+0.955...(B)

2. The first retardation element is a positive A plate that imparts an in-plane retardation of approximately λ / 4 at a wavelength of 550 nm. The display device according to claim 1 .

3. The second retardation element is a positive C plate that imparts a thickness direction retardation. The display device according to claim 1 .

4. the λ / 4 portion is a laminate in which a third retardation element and a first retardation element are laminated in this order from the light-reflective image display layer side, the first retardation element of the λ / 4 portion has a reverse wavelength dispersion and provides an in-plane retardation of approximately λ / 4; The third retardation element is an element that imparts a thickness direction retardation. The display device according to any one of claims 1 to 3.

5. the first retardation element of the λ / 4 portion is a positive A plate that provides a phase difference of approximately λ / 4 as an in-plane phase difference at a wavelength of 550 nm, The third retardation element is a positive C plate or a negative C plate that imparts a thickness direction retardation. The display device according to claim 4.

Citation Information

Patent Citations

  • Anti-reflective polarizing plate and device using thereof

    JP2006259694A

  • Member for manufacturing retardation film

    JP2010102288A

  • Polymerizable liquid crystal composition, optically anisotropic substance, and manufacturing method therefor

    JP2021002026A

  • Optical laminate

    JP2021009360A

  • Organic el display element comprising optical laminate

    WO2013137464A1